The shared custody in conflicting family relationships - Garay Molina, Ana Cecilia (2021)
Two of the family conflicts that most affect children are family violence and the separation of the parents (whether they are married or not): in these cases, the need arises to decide which of them will have custody of the minor children or if it will fall on both of them. Thanks to the formula of shared custody, which we analyze in this paper, the children can have a greater enjoyment of the presence and care of both parents, who have the best conditions to define the most appropriate custody regime for their children according to their particular circumstances. The exercise of shared custody by separated parents is more effective if they have reached an agreement. The judge are going to ratify or not the agreement established by the parents as he considers or not suitable for the welfare of the child or adolescent. The custody must be ruled by the greatest benefit of children and not by a sense of justice or equity towards the parents.